Nutritional Indices, Phytochemistry, and the In Vitro Antioxidant Activity of Carrot Fortified Tomato Concentrate - Olabisi Theresa Ademosun; Abiodun Humphrey Adebayo; Kolawole Oluseyi Ajanaku (Journal of Food Quality)
Researchers are constantly looking at the development of functional foods from local materials that offer both nutritional and therapeutic potentials. The study investigated the proximate composition, antioxidant capacity, and phytochemical profile of different compositions of formulations produced from tomato and carrot. The plant materials were sourced locally, dried to a uniform weight, and milled using a mechanical blender. Nutritional indices, viz., proximate analysis, were analyzed using a standard protocol. The phytocompounds present in the formulations and their in vitro antioxidant activities were analyzed using spectrophotometric methods. The results for proximate composition showed low moisture content in formulations (0.44 ± 0.015–0.54 ± 0.021%). The protein content of the formulations (16.51 ± 0.217–17.94 ± 0.134%) was significantly higher than that of carrot alone (8.41 ± 0.154%). Similarly, the crude fat was elevated in the formulations (0.31 ± 0.008–1.63 ± 0.017%) compared to tomato alone (0.10 ± 0.399). However, these values were lower than the values obtained for carrot alone (8.72 ± 0.009%). The energy value for the formulations ranged from 87.01 to 93.30 kcal, which was low compared to carrot alone (136.89 kcal). Phytochemical screening showed the presence of terpenoids, cardiac glycosides, saponins, phenols, flavonoids, and alkaloids in the studied formulations. Furthermore, the incorporation of carrot led to an increase in TPC, TFC, and alkaloid concentration. The pH values observed were around the neutral range, while lactic acid concentrations reduced following the incorporation of carrot. Trace element analysis showed improved iron and manganese concentrations in the formulation. Similarly, increased antioxidant ability was observed in the formulation. For sensory evaluation, reporters indicated good sensory parameters. Concluding, this study has shown that formulating concentrate from tomato and carrot showed improved nutritional potential and enormous antioxidant capacity that can be attributed to the presence of elevated total phenolics and flavonoid concentrations. Therefore, this formulation is warranted for improving the health of mankind.